1979
DOI: 10.1080/00913847.1979.11948525
|View full text |Cite
|
Sign up to set email alerts
|

Physical Profile of the Wrestlers at the 1977 NCAA Championships

Abstract: Differences in physical characteristics affect athletic performance, but the author says there are other more far-reaching implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
2
17
0
1
Order By: Relevance
“…In addition to morphological aspects, previous studies on muscle function in wrestlers have shown that the strength and endurance capabilities of the upper body rather than the lower body plays an important role in wrestling performance (Nagle et al 1975;Stine et al 1979;Horswill et al 1992). The bene®t of resistance training in both muscle size and function has been shown to depends to a great extent on the content of the training regimens performed (Moss et al 1997;Schimidtbleicher and Buehrle 1987).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to morphological aspects, previous studies on muscle function in wrestlers have shown that the strength and endurance capabilities of the upper body rather than the lower body plays an important role in wrestling performance (Nagle et al 1975;Stine et al 1979;Horswill et al 1992). The bene®t of resistance training in both muscle size and function has been shown to depends to a great extent on the content of the training regimens performed (Moss et al 1997;Schimidtbleicher and Buehrle 1987).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, it has been shown that wrestling requires the participants have superior cardiovascular ®tness as well as muscle strength and endurance (Nagle et al 1975;Stine et al 1979). It has been found that the changes in muscle function with training re¯ect the type of muscle activity during exercise (Sale and MacDougall 1981).…”
Section: Introductionmentioning
confidence: 97%
“…In the wrestling group analyzed, the predictive ability of maximal strength, muscle power and crank-arm Wingate power to distinguish wrestling success remained significant after adjusting for fat-free mass, suggesting that the lean mass may contribute to the wrestling success, independent of training experience. Wrestling neuromuscular performance has been previously examined during isokinetic (Cisar et al 1987;Kraemer et al 2001;Sharratt et al 1986;Song and Garvie 1980;Stine et al 1979), isometric strength testing (Kraemer et al 2001;Sharratt et al 1986;Song and Garvie 1980;Utter et al 2002) and even with highly specific exercises like the isometric ''bear hug'' designed to simulate many upper-body holds used by wrestlers (Kraemer et al 2001). Unfortunately, a small number of researchers have examined dynamic muscle strength and muscle power profiles in exercises closely related to specific skills in wrestling (Mirzaei et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have also reported that, although aerobic performance may be a basic requirement for wrestlers, it cannot be considered as a critical component of success in this sport (Horswill 1992;Horswill et al 1992;Sharratt et al 1986;Stine et al 1979;Yoon 2002).…”
Section: Introductionmentioning
confidence: 96%
“…At the U.S. college level, participants in the NCAA tournament lost 10 to 12% of their preseason body weight or, in absolute amounts, approximately 9 kg (69). More recent research surveying collegiate wrestlers for weekly practices reported similar magnitudes of weight loss: 85% of the college wrestlers lost between 2.7 and 9.1 kg each week (66).…”
Section: Magnitudementioning
confidence: 56%